2019
DOI: 10.1039/c9gc01806a
|View full text |Cite
|
Sign up to set email alerts
|

Are lignin-derived carbon fibers graphitic enough?

Abstract: The extent of graphitization is an overlooked limitation to lignin-derived carbon fiber development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 61 publications
(104 reference statements)
1
62
0
Order By: Relevance
“…However, these findings are in complete agreement with reported Raman results on the carbon fibres obtained from lignin 4 , 20 . Moreover, it is reported that the higher molecular weight of lignin enhances the graphitic structure and mechanical performance 94 .…”
Section: Resultsmentioning
confidence: 99%
“…However, these findings are in complete agreement with reported Raman results on the carbon fibres obtained from lignin 4 , 20 . Moreover, it is reported that the higher molecular weight of lignin enhances the graphitic structure and mechanical performance 94 .…”
Section: Resultsmentioning
confidence: 99%
“…Another noticeable finding is how lignin carbonizes and forms the carbon structure. Lignin is a non-graphitizable compound, so the carbon fibres from lignin cannot achieve high mechanical strength without any treatment to improve the graphitic structure (Sagues et al, 2019) The skin-core phenomenon, however, was observed in Zone 2 but disappeared in Zone 4 and was attributed to the incomplete stabilization of precursor fibres. It was found that this led to the formation of hollow carbon fibres after carbonization which have very high surface areas, providing promise for applications in batteries, catalyst carriers or membranes (Liu, Chae, Choi, & Kumar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the arc discharge treatment introduced a defective/porous structure to the fibres. The (100) crystallite size L c was calculated using the Debye formula and the value was 7.1 nm, which is similar to the L c of lignin fibres thermally carbonised at 1000 °C [ 50 ].…”
Section: Resultsmentioning
confidence: 99%